Contextualising policy work: policy enactment and the specificities of English secondary schools. Issue 4 (3rd July 2020) - Maguire, Meg; Gewirtz, Sharon; Towers, Emma; Neumann, Eszter
ABSTRACT: This paper returns to a long-standing theme in education research, the ways in which 'contextual factors impact on what schools do, as well as directly on what pupils achieve' (Lupton, 2004, 4). Drawing on a project designed to explore the early effects of reforms to national examinations, the curriculum for 14−16 year olds and school accountability measures in English secondary schools, this paper considers the perceptions and experiences of teachers currently charged with enacting these reforms specifically in the light of their situated school realities in three different settings. A case is made for a contextually sensitive approach towards policy making and policy enactment that takes account of some of the more nuanced distinctions among schools' contextual positionings.